2013
DOI: 10.14233/ajchem.2013.15145
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of Methylene Blue from Aqueous Solution Using Mg-Fe-Al Layered Double Hydroxides with H2O2

Abstract: Layered double hydroxides (LDH) or hydrotalcite, also classified to the type of anionic clays, are basic solid materials formed by divalent metal cation hydroxide layers with the brucite structure 1,2 .Layered double hydroxides (LDH) or hydrotalcite, also classified to the type of anionic clays, are basic solid materials formed by divalent metal cation hydroxide layers with the brucite structure 1,2 . The layers contain metal ions of at least two different oxidation states. The most common case of diand trival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…(2017) reported that 125 mg L -1 AgNPs composites derived from waste tea extract removed approximately 74% of low-concentration MB (0.008 mM) within 50 min at pH 7.5 in the presence of 294 mM H2O2. In Thao & Trang (2013), high concentration of MB (9.4 mM) was degraded by 80% after 50 min using a large amount of catalyst (1000 mg L -1 ) and high H2O2 concentration (132 mM). MnO2-templeted Fe oxide-coated diatomite at dose of 100 mg L -1 exhibited the photodegradation efficiency of 77.5% at 0.06 mM MB under UV irradiation for 120 min using relatively high H2O2 concentration (90 mM).…”
Section: Effects Of Temperature Catalyst Dose Ph and Molar Ratio Of H...mentioning
confidence: 99%
“…(2017) reported that 125 mg L -1 AgNPs composites derived from waste tea extract removed approximately 74% of low-concentration MB (0.008 mM) within 50 min at pH 7.5 in the presence of 294 mM H2O2. In Thao & Trang (2013), high concentration of MB (9.4 mM) was degraded by 80% after 50 min using a large amount of catalyst (1000 mg L -1 ) and high H2O2 concentration (132 mM). MnO2-templeted Fe oxide-coated diatomite at dose of 100 mg L -1 exhibited the photodegradation efficiency of 77.5% at 0.06 mM MB under UV irradiation for 120 min using relatively high H2O2 concentration (90 mM).…”
Section: Effects Of Temperature Catalyst Dose Ph and Molar Ratio Of H...mentioning
confidence: 99%
“…LDH is a cheap hydrotalcite‐like compound, characterized by a 2D flat network structure with a formula [M 1‐x 2+ M x 3+ (OH − ) 2 ] x+ (A n− ) x/n mH 2 O in which M 2+ and M 3+ refers to metal cations, such as Mg 2+ , Co 2+ , Ni 2+ , Cu 2+ , Zn 2+ , and Al 3+ , Fe 3+ , Cr 3+ , Co 3+ , respectively, and A n− represents organic or inorganic inter layer anions . In the last years, LDHs based catalysts were proposed for many environmental applications, including catalytic wet peroxide oxidation and catalytic ozonation, Fenton and Fenton‐like processes as well as photo‐Fenton . It has been reported that LDHs exhibited good performances for Fenton‐like reactions due to strong metal synergic interactions and low metal leaching compared to other solid catalysts .…”
Section: Introductionmentioning
confidence: 99%